MIędzymiastowy mecz bokserski Częstochowa-Gdynia. ([S.l. : s.n.], 1946)
Afisz inf. o meczu 20.06.1946 r. w budynku Dworca Morskiego w Gdyni.
Keywords: Boks -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne